Assessing Four Budget-Balancing Strategies in Higher Education - Hauptman, Arthur M. (International Higher Education, 2010)
Higher education institutions currently face serious challenges from cutbacks in government funding worldwide. In responce to this, four strategies are available: capping enrollments and cutting costs, changing the mix of enrollments, increasing tuition fees for existing students, and increasing enrollments while maintaining current tuition-fee levels. Institutions need to decide their response based on their institutional conditions.